2002
DOI: 10.1142/s0218271802002153
|View full text |Cite
|
Sign up to set email alerts
|

Plane-Symmetric Inhomogeneous Viscous Fluid Cosmological Models With Electromagnetic Field

Abstract: We consider a magnetic cylindrically symmetric universe with a plane-symmetric inhomogeneous viscous fluid cosmological model with electromagnetic field. The viscosity coefficient of bulk viscous fluid is assumed to be a power function of mass density. To get a determinate solution, we assume the free gravitational field to be Petrov type-II non-degenerate. Without assuming any ad hoc law, we obtain a cosmological constant as a decreasing function of time. The behaviour of the electromagnetic field tensor toge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Singh et al (1990) obtained inhomogeneous cosmological models of perfect fluid distribution with electro-magnetic field. Recently, Pradhan and Pandey (2003a, 2003b, Pradhan et al (2002Pradhan et al ( , 2007aPradhan et al ( , 2007b have investigated plane-symmetric inhomogeneous cosmological models in various contexts. Cylindrically symmetric space-time play an important role in the study of the universe on a scale in which anisotropy and inhomogeneity are not ignored.…”
Section: Introductionmentioning
confidence: 99%
“…Singh et al (1990) obtained inhomogeneous cosmological models of perfect fluid distribution with electro-magnetic field. Recently, Pradhan and Pandey (2003a, 2003b, Pradhan et al (2002Pradhan et al ( , 2007aPradhan et al ( , 2007b have investigated plane-symmetric inhomogeneous cosmological models in various contexts. Cylindrically symmetric space-time play an important role in the study of the universe on a scale in which anisotropy and inhomogeneity are not ignored.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that β 2 has similar behaviour as the cosmological constant which decreases during expansion of universe. Several authors [53][65] have considered the relation β ∼ 1 t for study of cosmological models in different context.…”
Section: Physical Consequences Of the Modelsmentioning
confidence: 99%
“…This theory suggests a positive way to solve the missing matter problem in non-flat FRW cosmologies. The effect of bulk viscosity on cosmological evolution has been investigated by a number of authors in the context of general theory of relativity [4][5][6][7][8][9][10][11][12]. The nature of cosmological solution for homogenous cosmological model was investigated by Belinsky et al [13] and shown that viscosity can not remove the cosmological singularities but result in a qualitatively new behaviour of the solution near singularity.…”
Section: Introductionmentioning
confidence: 99%